2009
DOI: 10.1172/jci37028
|View full text |Cite
|
Sign up to set email alerts
|

The diabetes gene Pdx1 regulates the transcriptional network of pancreatic endocrine progenitor cells in mice

Abstract: Heterozygous mutations in the gene encoding the pancreatic homeodomain transcription factor pancreatic duodenal homeobox 1 (PDX1) are associated with maturity onset diabetes of the young, type 4 (MODY4) and type 2 diabetes. Pdx1 governs the early embryonic development of the pancreas and the later differentiation of the insulin-producing islet β cells of the endocrine compartment. We derived a Pdx1 hypomorphic allele that reveals a role for Pdx1 in the specification of endocrine progenitors. Mice homozygous fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
116
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 63 publications
(85 reference statements)
14
116
1
2
Order By: Relevance
“…Furthermore, Sox9 occupancy regions on the Ngn3 gene promoter have been identified (104,106). In addition, Sox9 may also regulate Ngn3 via Pdx1 (107,108). (In a seeming paradox, Sox9 also induces Hes1 expression [46], perhaps as a means of limiting its action on Ngn3.…”
Section: Nsc Biology Suggests the Involvement Of Noncanonical Signalimentioning
confidence: 99%
“…Furthermore, Sox9 occupancy regions on the Ngn3 gene promoter have been identified (104,106). In addition, Sox9 may also regulate Ngn3 via Pdx1 (107,108). (In a seeming paradox, Sox9 also induces Hes1 expression [46], perhaps as a means of limiting its action on Ngn3.…”
Section: Nsc Biology Suggests the Involvement Of Noncanonical Signalimentioning
confidence: 99%
“…Some of these transcription factors regulate complex transcriptional programmes of gene expression by acting on pancreatic cell specific target gene networks [15,16]. Furthermore, in combination with other transcription factors present in mature cells, they interact co-ordinately on the insulin gene promoter to regulate insulin gene expression [4,17].…”
Section: Introductionmentioning
confidence: 99%
“…A number of positive regulators of NGN3, such as PDX1 (Miyazaki et al 2004, Oliver-Krasinski et al 2009), HNF6 (Jacquemin et al 2000), SOX9 (Lynn et al 2007), FOXA2 (Lee et al 2001) and hepatocyte nuclear factor 1β (HNF1β) (Maestro et al 2003) have been identified in the developing pancreas. The expression of NGN3 was drastically reduced in the embryonic pancreata of Glis3 −/− mice both at mRNA and protein levels, compared to that in Glis3 +/+ mice, whereas GLIS3 overexpression significantly upregulated the Ngn3 mRNA in pancreatic ductal cells.…”
Section: Immunostaining Indicated That the Numbers Of All Types Of Enmentioning
confidence: 99%